Selected Topics from a Matched Study between a Face-to-face Section and a Real-Time Online Section of a University Course - Lobel, Mia; Neubauer, Michael; Swedburg, Randy (International Review of Research in Open and Distributed Learning, 2005)
Two sections of an interpersonal skills building university course were observed for the purposes of this matched study. The face-to-face (F2F) section was in a classroom on the Concordia University campus in Montreal, Canada, while the non-turn-taking real-time online section used a Web application, LBD eClassroom© designed specifically for highly interactive large size classes and meetings. Two sections used the same instructor, facilitators, pedagogy, and course content. This study revealed a unique pattern of non-turn-taking synchronous interaction in the online section. Online students were found to be more likely to participate and express themselves. Interaction of online participants led to the creation of a group entity – a polis – a cornerstone for collaborative group learning. In contrast, in the F2F section, interaction followed the traditional classroom pattern – centered on the teacher or expert, resulting in fewer students interacting, and hence, lower interaction overall. In sum, during these three hour sessions, it was found that the nature of online non-turn-taking environment afforded online students more time to express themselves compared to students learning the same material F2F.